Measurement of quasielastic-like neutrino scattering at ∼3.5 GeV on a hydrocarbon target - Ruterbories, D.; Hurtado, K.; Osta, J.; Akbar, F.; Aliaga, L.; Andrade, D.A.; Ascencio-Sosa, M.V.; Bashyal, A.; Bercellie, A.; Betancourt, M.; Bodek, A.; Budd, H.; et al. (American Physical Society, 2019)
MINERvA presents a new analysis of neutrino induced quasielastic-like interactions in a hydrocarbon tracking target. We report a double-differential cross section using the muon transverse and longitudinal momentum. In addition, differential cross sections as a function of the square of the four-momentum transferred and the neutrino energy are calculated using a quasielastic hypothesis. Finally, an analysis of energy deposited near the interaction vertex is presented. These results are compared to modified genie predictions as well as a NuWro prediction. All results use a data set produced by $3.34\ifmmode\times\else\texttimes\fi{}{10}^{20}$ protons on target creating a neutrino beam with a peak energy of approximately 3.5 GeV.
Keywords: Neutrino; Physics; Nuclear physics; Muon; Hadron; Particle physics; https://purl.org/pe-repo/ocde/ford#1.03.03